Formulasi Makanan Khas Seruit dari Lampung dengan Penambahan Ikan Gabus (Channa striata) Sebagai Sumber Protein: Formulation of Seruit Indigenous Food from Lampung with the Addition of Snakehead Fish (Channa striata) as a Source of Protein - Bertalina, Bertalina; Indriyani, Reni; Sudarmi, Sudarmi; Nugroho, Arie; Yunianto, Andi Eka (Amerta Nutrition, 2025)
Background: Seruit is an indigenous food in Lampung. The dish typically consists of a combination of seafood, vegetables, and spices that are stir-fried together to create a savory and aromatic dish beloved by locals and visitors alike. The key ingredient in seruit is the use of fresh seafood such as shrimp, squid, and fish. Objectives: The study aimed to determine a formula based on acceptability and macronutrient content, especially proteins. Methods: The study used a completely randomized experimental design. Seruit was a typical Lampung chili sauce, consisting of shrimp paste chili sauce supplemented with grilled snakehead fish meat. The seruit formulation used in this study consisted of a mixture of 30, 40, and 50 g of chili sauce and 70, 60, and 50 g of snakehead fish. Duncan’s Multiple Range Test (DMRT) was used to analyze organoleptic. Proximate test was used to determine the content of water, ash, crude fiber, carbohydrates, protein, and fat. Results: The acceptability was conducted by 30 semi-trained panelists with the selected formula, namely F3 with a mixture of 50 g of snakehead fish with color indicators (3.50±1.09), aroma (3.72±0.88), taste (3.87±0.94), and texture (3.62±1.02). 100g of harpoon contains 19.67% water content, 1.18% ash content, 2.63% crude fiber, 12.36% protein, 3.17% fat, and 60.98% carbohydrates. Seruit with F3 formula was chosen by the panelists and is a high source of protein. Conclusions: Seruit formula F3 with the addition of 50 g grilled snakehead fish is the selected formula and has potential as a local food source of protein that can be served in the daily diet according to a balanced nutritional diet.